Nutritional attitudes of professional women volleyball players: a cross-sectional study from Türkiye - Sahin, Oktay; Guler, Vesile Sahiner; Turan, Mehmet Behzat; Yoka, Keziban; Yoka, Osman; Polat, Yahya (Frontiers in Nutrition, 2025)
BackgroundNutritional habits are a critical factor influencing the performance and recovery of professional athletes. Understanding how demographic variables affect nutrition-related attitudes is essential for developing targeted interventions.ObjectiveThis study examined the nutritional attitudes of professional female volleyball players in Türkiye based on various demographic characteristics.MethodsThe study included 386 licensed female volleyball players from the Turkish Women's Volleyball Super League, First League, and Second League. Data were collected using a demographic questionnaire and the Attitude Scale for Healthy Nutrition. Normality was assessed using the Kolmogorov-Smirnov test and skewness-kurtosis values. Statistical analyses included t-tests, ANOVA, LSD post-hoc tests, and partial correlation.ResultsSignificant differences in nutritional attitudes were found based on league level, smoking status, years of experience, and income level (p < 0.01). No significant differences were observed based on education level. Among the sub-dimensions, the malnutrition component showed no significant differences across most variables. Super League athletes scored significantly higher in nutritional knowledge and positive nutritional behaviors.ConclusionThe nutritional attitudes of professional volleyball players vary considerably according to key demographic factors. These findings highlight the importance of targeted nutrition education, particularly for lower-league athletes, to enhance performance and reduce disparities in nutritional knowledge.